Utilization of Azolla Flour (Azolla microphylla) Fermentation in Diet to Increase Growth of Red Tilapia (Oreochromis niloticus) - Radiatul Husnaini; Indra Suharman; Adelina Adelina (Universitas Riau, 2021)
This research was conducted from January - March 2020. The aimed of this research was to evaluate the effect of using fermented A. microphylla flour in the diet on feed digestibility, feed efficiency and growth of red tilapia, and the best percentage of A. microphylla flour fermentation in the diet to increase feed efficiency and growth of red tilapia. This study used a one-factor completely randomized design (CRD) with 5 treatments and 3 replications. The treatments in this study were P0 (0% FTA), P1 (25% FTA), P2 (50% FTA), P3 (75% FTA), P4 (100% FTA) in feed. Diet as much as 10% of the weight of the biomass is given three times a day, namely at 07.00, 12.00 and 17.00 WIB. The red tilapia used were 5.50 ± 0.71 cm in size with an average weight of 1.27 ± 0.08g and a stocking density of 25 fish /m3. The results showed that giving azola leaf flour fermented could increase the growth and survival of red tilapia. The use of 25% fermented A. microphylla leaf meal (P1) gave the best results for the feed digestibility value of 75.96%, 76.59% protein digestibility, 62.07% feed efficiency, 85.36% protein retention, specific growth rate 4, 31% and the cost of the test feed is Rp. 8,310.